Signs of innate immune activation and premature immunosenescence in psoriasis patients - Liisi Šahmatova (Nature Portfolio, 2017)
Abstract Psoriasis is a chronic inflammatory disease that affects skin and is associated with systemic inflammation and many serious comorbidities ranging from metabolic syndrome to cancer. Important discoveries about psoriasis pathogenesis have enabled the development of effective biological treatments blocking the T helper 17 pathway. However, it has not been settled whether psoriasis is a T cell-mediated autoimmune disease or an autoinflammatory disorder that is driven by exaggerated innate immune signalling. Our comparative gene expression and hierarchical cluster analysis reveal important gene circuits involving innate receptors. Innate immune activation is indicated by increased absent in melanoma 2 (AIM2) inflammasome gene expression and active caspase 1 staining in psoriatic lesional skin. Increased eomesodermin (EOMES) expression in lesional and non-lesional skin is suggestive of innate-like virtual memory CD8+ T cell infiltration. We found that signs of systemic inflammation were present in most of the patients, correlated with the severity of the disease, and pointed to IL-6 involvement in the pathogenesis of psoriatic arthritis. Among the circulating T cell subpopulations, we identified a higher proportion of terminally differentiated or senescent CD8+ T cells, especially in patients with long disease duration, suggesting premature immunosenescence and its possible implications for psoriasis co-morbidities.